A kind of high thermal strength and high thermal conductivity coated sand and preparation method thereof

By constructing a new raw sand aggregate and modified binder system, high-thermal-strength and high-thermal conductivity coating sand was prepared, which solved the problem of insufficient performance of traditional coating sand in the production of high-temperature, high-pressure or irregular-shaped castings, achieved higher thermal strength and thermal conductivity, and reduced the occurrence of shelling defects.

CN119747579APending Publication Date: 2025-04-04JIANGXI TEXIN IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510047161.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Traditional coated sand is difficult to meet performance requirements in the production of high-temperature, high-pressure or irregular-shaped castings. The sand core often falls off due to unreasonable mold design, uneven core box temperature, or low melting point and low thermal strength of the phenolic resin film, resulting in the dehulling defect.

Method used

By constructing a new raw sand aggregate and modified binder system, high-thermal resins are used to combine modified zirconium, silicon and cresol resins, and combined with special curing agents and admixtures, high-thermal coating sand is prepared.

Benefits of technology

It realizes excellent thermal strength and thermal conductivity of coated sand, and can be suitable for the production of high-temperature, high-pressure and irregular-shaped castings, reducing the occurrence of shelling defects, and improving the accuracy and surface quality of castings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention discloses a high thermal strength and high thermal conductivity coated sand and a preparation method thereof, and belongs to the technical field of coated sand casting. The raw materials of the high thermal strength and high thermal conductivity coated sand of the present invention include by weight: 80-100 parts of raw sand aggregate, 5.2-7.2 parts of modified urea-formaldehyde resin, 1-1.5 parts of curing agent, 0.5-1 parts of lubricant, and 1.5-2.5 parts of additive; the modified urea-formaldehyde resin is a urea-formaldehyde resin composite-modified by zirconium, silicon, and cresol resin. The present invention constructs a new raw sand aggregate and a modified binder system, and at the same time cooperates with a special curing agent and an additive, so that the prepared coated sand has both excellent thermal strength and thermal conductivity, can adapt to the current production of high temperature, high pressure and irregular shape castings, and has good market competitiveness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coated sand casting, and specifically relates to a high thermal strength and high thermal conductivity coated sand and a preparation method thereof. Background Art

[0002] Coated sand refers to sand that is coated with a layer of polymer resin film on its surface before use. Casting molding is its main application direction. Currently in the foundry industry, coated sand is an important molding material, and its performance directly affects the quality and production efficiency of castings. With the continuous advancement of industrial technology and continuous innovation in casting technology, people's performance requirements for coated sand are also increasing. Traditional coated sand is often difficult to meet the requirements in the production of certain high-temperature, high-pressure or increasingly irregular-shaped castings. Due to unreasonable mold design, uneven core box temperature, or low melting point and low thermal strength of phenolic resin film, the sand core often falls off the mold during the casting process, forming shelling defects.

[0003] Thermal strength refers to the ability of a material to withstand high temperatures. For coated sand, the higher the thermal strength, the stronger its ability to resist high temperatures and pressures during the casting process, so that it can better maintain the shape and dimensional stability of the sand core. High thermal strength coated sand can reduce the deformation and breakage of the sand core at high temperatures and improve the precision and surface quality of the casting. Thermal conductivity refers to the ability of a material to transfer heat. The thermal conductivity of coated sand directly affects the cooling rate and temperature distribution of the casting. Excellent thermal conductivity can speed up the cooling rate of the casting, reduce the occurrence of thermal cracks and deformation, and improve the dimensional stability and internal quality of the casting. On the other hand, there is a certain correlation between the thermal strength and thermal conductivity of coated sand. High thermal strength coated sand generally has a lower thermal conductivity, and a lower thermal conductivity will cause the cooling rate of the casting to be too slow, especially for irregular castings, which will significantly increase its internal pores and shrinkage defects.

[0004] Based on this, comprehensively considering the balance between thermal strength and thermal conductivity, and developing a coated sand with excellent thermal strength and thermal conductivity is of great significance for the current production of high-temperature, high-pressure and irregular-shaped castings. Summary of the invention

[0005] In view of the problems raised by the background technology, the purpose of the present invention is to provide a high thermal strength and high thermal conductivity coated sand and a preparation method thereof. The present invention constructs a new raw sand aggregate and a modified binder system, and at the same time cooperates with a special curing agent and an admixture, so that the prepared coated sand has both excellent thermal strength and thermal conductivity, can adapt to the current production of high temperature, high pressure and irregular shape castings, and has good market competitiveness.

[0006] In order to achieve the above object, the present invention specifically adopts the following technical solutions: The present invention provides a high thermal strength and high thermal conductivity coated sand, wherein the raw materials of the coated sand include the following components by weight: 80-100 parts of raw sand aggregate, 5.2-7.2 parts of modified urea-formaldehyde resin, 1-1.5 parts of curing agent, Lubricant 0.5-1 part, 1.5-2.5 parts of admixture; The modified urea-formaldehyde resin is a urea-formaldehyde resin compositely modified by zirconium, silicon and cresol resin.

[0007] Preferably, the raw sand aggregate is composed of quartz sand and zirconium ore sand in a mass ratio of (90-99): (1-10); wherein quartz sand SiO 2 The content is not less than 95%, the AFS particle size is 60-70, the chromium ore sand ZrO 2 The content is 61%-64%, and the AFS particle size is 55-65.

[0008] The present invention uses quartz sand doped with chromium ore sand as raw sand aggregate. Since chromium ore sand has a higher melting point and thermal conductivity, it can reach a high strength state faster under the same conditions and has a higher bonding strength. The thermal expansion coefficient of chromium ore sand is small, which helps to reduce deformation and cracks during the cooling process of the casting, and can effectively prevent sand sticking and refine the crystal structure. Based on comprehensive considerations of cost and performance, the present invention uses quartz sand and zirconium ore sand in a mass ratio of (90-99): (1-10) to form raw sand aggregate, providing a basis for preparing high thermal strength and high thermal conductivity.

[0009] Preferably, the specific method for composite modification of urea-formaldehyde resin by zirconium, silicon and cresol resin is as follows: first, urea, formaldehyde solution and sodium hydroxide are mixed, and at the same time, an ethanol dispersion of tetrakis(2,4-pentanedione)zirconium and ethyl orthosilicate is added thereto, and the temperature is raised to 75-85°C and refluxed to obtain a urea-formaldehyde resin prepolymer, and then the urea-formaldehyde resin prepolymer is blended with cresol resin and methyltriethoxysilane, and then vacuum is evacuated to obtain a composite modified urea-formaldehyde resin.

[0010] For the production of high-temperature, high-pressure and irregular-shaped castings, conventional phenolic resins can no longer meet the performance requirements due to their poor fluidity and low heat resistance. The present invention first uses tetrakis(2,4-pentanedione)zirconium and ethyl orthosilicate to prepare zirconium- and silicon-modified urea-formaldehyde resin prepolymers, and then blends them with cresol resin and methyltriethoxysilane to prepare composite modified urea-formaldehyde resins. The modification based on zirconium and silicon can modify the resin structure, effectively ensure the air permeability and fluidity of urea-formaldehyde resin under high temperature and high pressure, thereby improving the processing performance and precision of complex castings, and at the same time helping to improve the thermal conductivity of coated sand; and further blending of cresol resin and methyltriethoxysilane can greatly improve the heat resistance of coated sand, and prevent defects such as sand sticking, thermal cracking, and pores from occurring during high-temperature casting of coated sand. The composite synergistic modification system of the present invention effectively improves the thermal stability and strength of urea-formaldehyde resin, thereby being able to give the prepared coated sand higher mechanical strength and stability, enabling it to withstand high temperature and high pressure and uneven stress in the complex sand core casting process, thereby being able to ensure the dimensional accuracy and surface quality of the casting.

[0011] Preferably, in the raw materials for preparing the urea-formaldehyde resin prepolymer, the mass ratio of urea, formaldehyde, tetrakis(2,4-pentanedione)zirconium and tetraethyl orthosilicate is 100:(70-90):(0.3-1):(2-4).

[0012] Preferably, the mass ratio of urea-formaldehyde resin prepolymer, cresol resin and methyltriethoxysilane is 100:(1.2-1.8):(1-4); the mixing conditions are: pH 7.5-9.5, temperature 85-95° C., and time 1-2 h.

[0013] Preferably, the curing agent is composed of hexamethylenetetramine and diethylenetriamine in a mass ratio of 10:(0.1-0.6). Preferably, the additive is glass powder, wherein Na 2 SiO 3 With CaSiO 3 The content is not less than 60%.

[0014] Based on the above raw sand and modified urea-formaldehyde resin system, the present invention further adopts urotropine and diethylenetriamine to form a special modified curing agent with fast polymerization rate. The urotropine doped with diethylenetriamine can induce a more complex cross-linking reaction with the above modified urea-formaldehyde resin of the present invention to form a more compact and stable network structure, further improving the overall strength and heat resistance of the sand mold; at the same time, glass powder is used as an additive to mix the sand synchronously with the curing agent, which can enhance the bonding force between the sand particles, resin and other components and improve the overall strength. In addition, the glass powder can also form a dense protective film under high temperature and high pressure, which not only enhances the high temperature resistance of the coated sand, but also further improves the surface finish of the casting.

[0015] The present invention also provides a method for preparing the above-mentioned high thermal strength and high thermal conductivity coated sand, comprising the following steps: Step 1: weigh the raw sand aggregate, modified urea-formaldehyde resin, curing agent, lubricant and admixture according to the proportion and set aside; Step 2: Heat the raw sand aggregate to 140℃-170℃, transfer it to a sand mixer, add modified urea-formaldehyde resin and mix for 1.2min-1.8min; Step 3: After the temperature of the mixture in step 2 is cooled to 125°C-135°C, add the admixture and curing agent and mix the sand for 0.9min-1.3min; Step 4: After the temperature of the mixture in step 3 cools to 85-90°C, add lubricant and mix the sand for 0.5min-1.0min. After the mixture is mixed, immediately release the sand, crush and screen it to obtain coated sand.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention solves the problem that the resin film of the existing conventional phenolic resin coated sand has a low melting point and low thermal strength, which causes the sand core to form shelling defects during the casting process, and provides a urea-formaldehyde resin coated sand with excellent thermal strength and thermal conductivity. It ensures high thermal strength while having a high thermal conductivity coefficient, and can be well applied to the current production of high-temperature, high-pressure and irregular-shaped castings, effectively expanding the application range of the coated sand. DETAILED DESCRIPTION

[0017] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.

[0018] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0019] Example 1 A method for preparing high thermal strength and high thermal conductivity coated sand, comprising the following steps: 1. Weigh urea, formaldehyde, tetrakis(2,4-pentanedione) zirconium and ethyl orthosilicate in a mass ratio of 100:82:0.7:3, prepare formaldehyde into a 36.5% aqueous solution, add urea and sodium hydroxide to adjust the pH to 8.0 (keep the pH unchanged in the subsequent process), and add tetrakis(2,4-pentanedione) zirconium and ethyl orthosilicate ethanol dispersion to it, heat to 80°C and reflux to obtain urea-formaldehyde resin prepolymer. Then add 1.5% of cresol resin and 2.5% of methyltriethoxysilane to the urea-formaldehyde resin prepolymer, adjust the pH to 8.5, mix at 90°C for 1.5 hours, and then evacuate to obtain modified urea-formaldehyde resin.

[0020] 2. Take 90 parts of raw sand aggregate by weight (composed of quartz sand and zirconium ore sand in a mass ratio of 95:5, quartz sand SiO 2 Content 98%, AFS particle size 60-70, chromium ore ZrO 2 content 63%, AFS particle size 55-65), 6.2 parts of the above modified urea-formaldehyde resin, 1.3 parts of curing agent (composed of urotropine and diethylenetriamine in a mass ratio of 10:0.5, prepared into a 40% aqueous solution), 0.8 parts of lubricant (calcium stearate), glass powder (Na 2 SiO 3 42.2%, CaSiO 3 25.4% Remainder is SiO 2 and other impurities) 2 parts.

[0021] 3. Heat the raw sand aggregate to 150°C, transfer it to a sand mixer, add modified urea-formaldehyde resin and mix for 1.5 min; wait for the mixture to cool to 130°C, add glass powder and curing agent and mix for 1.1 min; wait for the mixture to cool to 88°C, add lubricant and mix for 0.8 min. After the mixture is cooled, immediately discharge the sand, crush and screen it to obtain coated sand.

[0022] Example 2 A method for preparing high thermal strength and high thermal conductivity coated sand, comprising the following steps: 1. Weigh urea, formaldehyde, tetrakis(2,4-pentanedione) zirconium and ethyl orthosilicate in a mass ratio of 100:70:0.8:4, prepare formaldehyde into a 36.5% aqueous solution, add urea and sodium hydroxide to adjust the pH to 7.5 (keep the pH unchanged in the subsequent process), and add tetrakis(2,4-pentanedione) zirconium and ethyl orthosilicate ethanol dispersion to it, heat to 75°C and reflux to obtain urea-formaldehyde resin prepolymer. Then add 1.2% of cresol resin and 4% of methyltriethoxysilane to the urea-formaldehyde resin prepolymer, adjust the pH to 8.5, mix at 90°C for 1.5 hours, and then evacuate to obtain modified urea-formaldehyde resin.

[0023] 2. Take 90 parts of raw sand aggregate by weight (composed of quartz sand and zirconium ore sand in a mass ratio of 90:10, quartz sand SiO 2 Content 98%, AFS particle size 60-70, chromium ore ZrO 2 content 63%, AFS particle size 55-65), 5.2 parts of the above modified urea-formaldehyde resin, 1.3 parts of curing agent (composed of urotropine and diethylenetriamine in a mass ratio of 10:0.1, prepared into a 40% aqueous solution), 0.8 parts of lubricant (calcium stearate), glass powder (Na 2 SiO 3 42.2%, CaSiO 3 25.4% Remainder is SiO 2 and other impurities) 2.5 parts.

[0024] 3. Heat the raw sand aggregate to 160°C, transfer it to a sand mixer, add modified urea-formaldehyde resin and mix it for 1.4 min; wait for the mixture to cool to 130°C, add glass powder and curing agent and mix it for 1 min; wait for the mixture to cool to 88°C, add lubricant and mix it for 0.6 min. After the mixture is finished, immediately discharge the sand, crush and screen it to obtain coated sand.

[0025] Example 3 A method for preparing high thermal strength and high thermal conductivity coated sand, comprising the following steps: 1. Weigh urea, formaldehyde, tetrakis(2,4-pentanedione) zirconium and ethyl orthosilicate in a mass ratio of 100:90:0.3:4, prepare formaldehyde into a 36.5% aqueous solution, add urea and sodium hydroxide to adjust the pH to 8.0 (keep the pH unchanged in the subsequent process), and add tetrakis(2,4-pentanedione) zirconium and ethyl orthosilicate ethanol dispersion thereto, heat to 80°C and reflux to obtain urea-formaldehyde resin prepolymer. Then add 1.5% by mass of cresol resin and 2.5% by mass of methyltriethoxysilane to the urea-formaldehyde resin prepolymer, adjust the pH to 8.5, mix at 90°C for 1.5 h, and then evacuate to obtain modified urea-formaldehyde resin.

[0026] 2. Take 90 parts of raw sand aggregate by weight (composed of quartz sand and zirconium ore sand in a mass ratio of 90:10, quartz sand SiO 2 Content 98%, AFS particle size 60-70, chromium ore ZrO 2 content 63%, AFS particle size 55-65), 7.2 parts of the above modified urea-formaldehyde resin, 1.3 parts of curing agent (composed of urotropine and diethylenetriamine in a mass ratio of 10:0.6, prepared into a 40% aqueous solution), 0.8 parts of lubricant (calcium stearate), glass powder (Na 2 SiO 3 42.2%, CaSiO 3 25.4% Remainder is SiO2 and other impurities) 1.5 parts.

[0027] 3. Heat the raw sand aggregate to 170°C, transfer it to a sand mixer, add modified urea-formaldehyde resin and mix for 1.2 min; wait for the mixture to cool to 135°C, add glass powder and curing agent and mix for 0.9 min; wait for the mixture to cool to 90°C, add lubricant and mix for 0.5 min. After the mixture is cooled, immediately discharge the sand, crush and screen it to obtain coated sand.

[0028] Example 4 A method for preparing high thermal strength and high thermal conductivity coated sand, comprising the following steps: 1. Weigh urea, formaldehyde, tetrakis(2,4-pentanedione) zirconium and ethyl orthosilicate in a mass ratio of 100:80:1:2, prepare formaldehyde into a 36.5% aqueous solution, add urea and sodium hydroxide to adjust the pH to 8.5 (keep the pH unchanged in the subsequent process), and add tetrakis(2,4-pentanedione) zirconium and ethyl orthosilicate ethanol dispersion to it, heat to 85°C and reflux to obtain urea-formaldehyde resin prepolymer. Then add 1.8% by weight of cresol resin and 1% by weight of methyltriethoxysilane to the urea-formaldehyde resin prepolymer, adjust the pH to 8.5, mix at 90°C for 1.5 hours, and then evacuate to obtain modified urea-formaldehyde resin.

[0029] 2. Take 90 parts of raw sand aggregate by weight (composed of quartz sand and zirconium ore sand in a mass ratio of 95:5, quartz sand SiO 2 Content 98%, AFS particle size 60-70, chromium ore ZrO 2 content 63%, AFS particle size 55-65), 6.2 parts of the above modified urea-formaldehyde resin, 1.3 parts of curing agent (composed of urotropine and diethylenetriamine in a mass ratio of 10:0.5, prepared into a 40% aqueous solution), 1 part of lubricant (calcium stearate), 1 part of glass powder (Na 2 SiO 3 42.2%, CaSiO 3 25.4% Remainder is SiO 2 and other impurities) 2 parts.

[0030] 3. Heat the raw sand aggregate to 140°C, transfer it to a sand mixer, add modified urea-formaldehyde resin and mix for 1.8 min; wait for the mixture to cool to 125°C, add glass powder and curing agent and mix for 1.2 min; wait for the mixture to cool to 85°C, add lubricant and mix for 1.0 min. After the mixture is cooled, immediately discharge the sand, crush and screen it to obtain coated sand.

[0031] Comparative Example 1 The step parameters are as in Example 1, except that thermoplastic phenolic resin is used as the binder instead of modified urea-formaldehyde resin.

[0032] Comparative Example 2 The step parameters are as in Example 1, except that in step 1, no tetraethyl orthosilicate is added to prepare the modified urea-formaldehyde resin.

[0033] Comparative Example 3 The step parameters are as in Example 1, except that tetrakis(2,4-pentanedione)zirconium is not added in step 1 to prepare the modified urea-formaldehyde resin.

[0034] Comparative Example 4 The step parameters are as in Example 1, except that in step 1, no cresol resin is added to prepare the modified urea-formaldehyde resin.

[0035] Comparative Example 5 The step parameters are as in Example 1, except that in step 1, no methyltriethoxysilane is added to prepare the modified urea-formaldehyde resin.

[0036] Comparative Example 6 Refer to the step parameters of Example 1, except that the coated sand raw material in step 2 does not include the additive glass powder.

[0037] Test example The performance of the sample coated sand prepared in the above embodiments and comparative examples was tested (testing standard JB / T 8583-2008), and the results are as shown in the following table (wherein the room temperature flexural strength test temperature is 20°C, the hot flexural strength test temperature is 232°C, and the high temperature flexural strength test is a simulated casting temperature of 1500°C).

[0038] Table 1 Test results of coated sand samples

[0039] In summary, the coated sand prepared by the process system of the present invention not only has high thermal conductivity but also excellent thermal strength, while the coated sand prepared by conventional phenolic resin only has high thermal conductivity and is not competent for the production of high-temperature, high-pressure and irregular-shaped castings. Although the adjustment of the urea-formaldehyde resin modification system of the present invention has little effect on the strength at room temperature, it reduces the thermal conductivity to varying degrees, especially significantly affecting the thermal strength.

[0040] The embodiments described above only express several preferred embodiments of the present invention, and the descriptions thereof are relatively specific and detailed, but are not intended to limit the present invention. It should be noted that for those skilled in the art, the present invention may also have various changes and modifications, and any modifications, equivalent substitutions, improvements, etc. made within the concept and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A high thermal strength and high thermal conductivity coated sand, characterized in that: The coated sand raw material comprises the following components by weight: 80-100 parts of raw sand aggregate, 5.2-7.2 parts of modified urea-formaldehyde resin, 1-1.5 parts of curing agent, Lubricant 0.5-1 part, 1.5-2.5 parts of admixture; The modified urea-formaldehyde resin is a urea-formaldehyde resin compositely modified by zirconium, silicon and cresol resin.

2. The high thermal strength and high thermal conductivity coated sand according to claim 1, characterized in that: The raw sand aggregate is composed of quartz sand and zirconium ore sand in a mass ratio of (90-99):(1-10); wherein the SiO2 content of the quartz sand is not less than 95%, and the AFS particle size is 60-70; the ZrO2 content of the chromium ore sand is 61%-64%, and the AFS particle size is 55-65.

3. The high thermal strength and high thermal conductivity coated sand according to claim 1, characterized in that: The specific method for composite modified urea-formaldehyde resin of zirconium, silicon and cresol resin is as follows: first, urea, formaldehyde solution and sodium hydroxide are mixed, and at the same time, tetrakis(2,4-pentanedione)zirconium and ethyl orthosilicate ethanol dispersion are added thereto, and the temperature is raised to 75-85°C and refluxed to obtain urea-formaldehyde resin prepolymer, and then the urea-formaldehyde resin prepolymer is blended with cresol resin and methyltriethoxysilane, and then vacuum is evacuated to obtain composite modified urea-formaldehyde resin.

4. The high thermal strength and high thermal conductivity coated sand according to claim 3, characterized in that: In the raw materials for preparing the urea-formaldehyde resin prepolymer, the mass ratio of urea, formaldehyde, tetrakis(2,4-pentanedione)zirconium and tetraethyl orthosilicate is 100:(70-90):(0.3-1):(2-4).

5. The high thermal strength and high thermal conductivity coated sand according to claim 3, characterized in that: The mass ratio of urea-formaldehyde resin prepolymer, cresol resin and methyltriethoxysilane is 100:(1.2-1.8):(1-4); the mixing conditions are: pH 7.5-9.5, temperature 85-95°C, and time 1-2 h.

6. The high thermal strength and high thermal conductivity coated sand according to claim 1, characterized in that: The curing agent is composed of hexamethylenetetramine and diethylenetriamine in a mass ratio of 10:(0.1-0.6).

7. The high thermal strength and high thermal conductivity coated sand according to claim 1, characterized in that: The additive is glass powder, and the content of Na2SiO3 and CaSiO3 thereof is not less than 60%.

8. The method for preparing the high thermal strength and high thermal conductivity coated sand according to any one of claims 1 to 7, characterized in that: The steps include: Step 1: weigh the raw sand aggregate, modified urea-formaldehyde resin, curing agent, lubricant and admixture according to the proportion and set aside; Step 2: Heat the raw sand aggregate to 140℃-170℃, transfer it to a sand mixer, add modified urea-formaldehyde resin and mix for 1.2min-1.8min; Step 3: After the temperature of the mixture in step 2 is cooled to 125°C-135°C, add the admixture and curing agent and mix the sand for 0.9min-1.3min; Step 4: After the temperature of the mixture in step 3 cools to 85-90°C, add lubricant and mix the sand for 0.5min-1.0min. After the mixture is mixed, immediately release the sand, crush and screen it to obtain the coated sand.